2021
DOI: 10.3389/fpls.2021.730181
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Weight Ensemble Framework for Yield Prediction of Winter Wheat Under Different Water Stress Treatments Using Unmanned Aerial Vehicle-Based Multispectral and Thermal Data

Abstract: Crop breeding programs generally perform early field assessments of candidate selection based on primary traits such as grain yield (GY). The traditional methods of yield assessment are costly, inefficient, and considered a bottleneck in modern precision agriculture. Recent advances in an unmanned aerial vehicle (UAV) and development of sensors have opened a new avenue for data acquisition cost-effectively and rapidly. We evaluated UAV-based multispectral and thermal images for in-season GY prediction using 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…The results revealed that repRVI performed best in grain yield assessment at the LGF stage, which is consistent with previous studies ( Hassan et al., 2019 ; Fei et al., 2021a ; Fei et al., 2021b ; Ganeva et al., 2022 ), because the LGF stage is close to maturity and the information in the UAVs field of view is mainly provided by the mature spikes. The signal is minimally affected by moisture and other green parts of the rice plant.…”
Section: Discussionsupporting
confidence: 91%
“…The results revealed that repRVI performed best in grain yield assessment at the LGF stage, which is consistent with previous studies ( Hassan et al., 2019 ; Fei et al., 2021a ; Fei et al., 2021b ; Ganeva et al., 2022 ), because the LGF stage is close to maturity and the information in the UAVs field of view is mainly provided by the mature spikes. The signal is minimally affected by moisture and other green parts of the rice plant.…”
Section: Discussionsupporting
confidence: 91%
“…Keywords clustering 4 biomass: Biomass is a common crop parameter based on remote sensing and with the rapid development of remote sensing technology biomass detection techniques have advanced tremendously with the rapid development of precision agriculture from 1980 to 2021. The rapid development of UAV technology, lightweight multispectral, and hyperspectral equipment has provided new tools for biomass detection and during these decades most of the studies on crop parameters were conducted based on spectral information and with the addition of 3D information technology the interplay of the two is a new progress in the detection of crop parameters ( Candiago et al, 2015 ; Näsi et al, 2018 ; Zhu et al, 2019a ; Fei et al, 2021 ; Jayakumari et al, 2021 ; Li et al, 2021 ; Yu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Precision agriculture has become a popular topic in recent years, and the development of nondestructive estimation technologies have provided new methods and means for crop growth estimation, presenting good application prospects. Previous studies have shown that images collected by sensors such as an RGB camera [ 17 ], a thermal infrared camera [ 18 ], a hyperspectral camera [ 19 ], and a CT scanner [ 20 ] can extract multiple image traits, and based on these image traits, prediction models of the leaf area index [ 21 ], leaf iron deficiency greening, and other indicators [ 22 , 23 ] can be established. Among the above-mentioned sensors, thermal infrared cameras work in the field environment, which is greatly affected by the ambient temperature and has an extremely low resolution [ 24 ].…”
Section: Introductionmentioning
confidence: 99%